The Living Donor Collective: A Scientific Registry for Living Donors. Issue 12 (22nd June 2017) - Kasiske, B. L.; Asrani, S. K.; Dew, M. A.; Henderson, M. L.; Henrich, C.; Humar, A.; Israni, A. K.; Lentine, K. L.; Matas, A. J.; Newell, K. A.; LaPointe Rudow, D.; Massie, A. B.; et al.
Abstract : In the setting of an overall decline in living organ donation and new questions about long‐term safety, a better understanding of outcomes after living donation has become imperative. Adequate information on outcomes important to donors may take many years to ascertain and may be evident only by comparing large numbers of donors with suitable controls. Previous studies have been unable to fully answer critical questions, primarily due to lack of appropriate controls, inadequate sample size, and/or follow‐up duration that is too short to allow detection of important risks attributable to donation. The Organ Procurement and Transplantation Network does not follow donors long term and has no prospective control group with which to compare postdonation outcomes. There is a need to establish a national living donor registry and to prospectively follow donors over their lifetimes. In addition, there is a need to better understand the reasons many potential donors who volunteer to donate do not donate and whether the reasons are justified. Therefore, the US Health Resources and Services Administration asked the Scientific Registry of Transplant Recipients to establish a national registry to address these important questions. Here, we discuss the efforts, challenges, and opportunities inherent in establishing the Living Donor Collective. Abstract : The Scientific Registry of Transplant Recipients, under contract to the U.S. Health Resources and Services Administration, will establish a registry of potential donor candidates and living organ donors to better understand long‐term outcomes. [Correction added on 17 November, 2017: "transplant candidates" was changed to "potential donor candidates"]